PHYTOCHEMICAL SCREENING AND ANTIMICROBIAL ACTIVITY OF BLUMEA MOLLIS (D.DON) MERRILL - V, JYOTHILEKSHMY; NAIR G, ANJALI; K, VYSHAK; R NAIR, RADHIKA; MURALIKRISHNAN, AMRITA; BANU, JIFITHA; PAPPACHEN, LEENA K (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this research was to carry out the preliminary phytochemical screening and to evaluate the antimicrobial activity of the methanolic extract of the Blumea mollis. Methods: In the present work, the phytochemicals of the whole plant were extracted using petroleum ether, chloroform, methanol, ethanol, and distilled water. These were then screened for triterpenes/steroids, alkaloids, anthraquinones, coumarins, flavonoids, saponins, tannins, and phenolic acids using standard methods. Further, the antimicrobial activity of the methanolic extract was determined using Gram-positive and negative bacteria. Agar well diffusion method was employed for antimicrobial activity study, and the zone of inhibition was found out. Results: The intensity of the color produced or the precipitate formed was used as the analytical response to these tests. Flavonoids, tannins, and phenolic acids showed positive results for phytochemical screening. The concentration of total phenols and flavonoids of the decoction was 45.5±0.2000 μg/ml gallic acid equivalent and 42.3±0.3606 μg/ml quercetin equivalent, respectively. Staphylococcus aureus, Escherichia coli, and Candida albicans were inhibited by the methanolic extract of B. mollis in agar well diffusion test. Conclusion: The results of the present study showed that the methanolic extract of B. mollis contains glycosides, phenolics, tannins, and flavonoids. Plant possesses significant antibacterial and antifungal property; the potent antimicrobial activity of the plant could be attributed to the presence of flavonoids and phenolic compounds in it.